PENGARUH ELEMEN EKOWISATA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE TAMAN HUTAN RAYA IR. H. DJUANDA - Waluya, Bagja; Jamil, Rima Sophal (Universitas Pendidikan Indonesia, 2016)
Forest tourism always improve itself to be better as like as the progressive of sustainable tourism and tourist has knew to go back to nature. The sustainable tourism well going on it is the ecotourism. One of the ecotourism area who famous is it Ir.H.Djuanda grand forest park. As a nature-based tourism Ir.H.Djuanda grand forest park need strategy to increase number of visitâ€™s, they using elements of ecotourism strategy. Elements of ecotourism as independent variable (X) is nature, education and sustainability, and dependent variable (Y) is visit decision. Sustainable and education differentiating ecotourism from â€œnature-based tourismâ€. This type of research was descriptive verificative research and sampling methode use was systematic random sampling with the amount of sampling was 100 domestic tourist who has visited Ir.H.Djuanda grand forest park. Techniques of data analysis and hypothesis testing used was multiple linear regression analysis. The result showed that the dimension of the element of ecotourism education and visit decision dimension on purchase timing at the lowest score if we compared to other dimension. However it can be concluded that the elements of ecotourism Ir.H.Djuanda grand forest park and the visit decision to Ir.H.Djuanda grand forest park in the category of avarage, and also elements of ecotourism has influence the visit decision.